2012
DOI: 10.1353/hpu.2012.0061
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Control Needs of 2-1-1 Callers in Missouri, North Carolina, Texas, and Washington

Abstract: Innovative interventions are needed to connect underserved populations to cancer control services. With data from Missouri, North Carolina, Texas, and Washington this study a) estimated the cancer control needs of callers to 2-1-1, an information and referral system used by underserved populations, b) compared rates of need to state and national data, and c) examined receptiveness to needed referrals. From October 2009 to March 2010 callers’ (N = 1408) cancer control needs were assessed in six areas: breast, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…The 2-1-1 Helpline is a telephone-delivered referral program to help link callers to local and affordable programs and services to meet their basic needs (e.g., housing, health, or social services). Based on a pilot study conducted in 2011, we found that the majority (70%) of 2-1-1 callers needed at least one cancer prevention service [48]. Many are unaware of existing health services or experience financial and transportation barriers.…”
Section: Research-tested Intervention Approaches In Hispanic Communitiesmentioning
confidence: 99%
“…The 2-1-1 Helpline is a telephone-delivered referral program to help link callers to local and affordable programs and services to meet their basic needs (e.g., housing, health, or social services). Based on a pilot study conducted in 2011, we found that the majority (70%) of 2-1-1 callers needed at least one cancer prevention service [48]. Many are unaware of existing health services or experience financial and transportation barriers.…”
Section: Research-tested Intervention Approaches In Hispanic Communitiesmentioning
confidence: 99%
“…2-1-1 is a nationally designated three-digit telephone information and referral service that connects callers to local health and social services. 4 These callers represent individuals with many basic needs and who are at increased risk for cancer and other chronic diseases based on their high rates of unemployment, low levels of income and education, 5 and African American or Hispanic race/ethnicity.…”
Section: Resultsmentioning
confidence: 99%
“…Future research can also assess the reliability of self-report in assessing whether participants contacted referrals. Although there is indication that cancer control needs among 2-1-1 callers are comparable across several states (Purnell et al, 2012), more research about characteristics of 2-1-1 callers at the national level would help determine the extent to which these findings may generalize to other populations.…”
Section: Discussionmentioning
confidence: 99%
“…The 2-1-1 system may also be a promising way of reaching underserved populations in order to reduce health disparities (Hall et al, 2012; Kreuter, 2012; Linnan, 2012). Callers to 2-1-1 have higher unmet cancer control needs compared to the general population; a survey of callers in four states found that over two-thirds had at least one unmet cancer control need (Purnell et al, 2012). Past work has shown that callers to 2-1-1 are generally receptive to answering questions about their health, and most are comfortable with receiving health information from 2-1-1 (Eddens et al, 2011).…”
mentioning
confidence: 99%